EFFECTIVENESS OF MUSIC THERAPY ON AGGRESSION AS AN ADJUNCT THERAPY - C.A. Jesna; Radhakrishnan; K Lalitha; Ramachandra; Sailaxmi Gandhi; Prasanthi Nattala; John Vijaysagar (Indian Journal of Psychiatric Nursing)
Knowledge on the effect of music therapy in person with mental illness is very important. The aim of the review is to discuss the articles pertaining to music therapy on aggression among person with mental illness. The review was based on studies conducted globally. Systematic search was conducted on a range of databases, citations were sought from relevant reviews and several websites were also included in the search, including those of MIND and Mental Health Foundation. MEDline, EMBASE and Psyc INFO were searched for studies published from 2000 January to 2015. Quantitative method and Descriptive approach were used for this reviewing 14 articles. Majority of the studies (11 out of 14, 78.57%) showed positive effects of music therapy on aggression, were as remaining 3 studies (21.42 %) not shown any effect on aggression. The present review also reveals that Group Active Music Therapy model (75%) was more effective than Group Receptive Music Therapy Model (66.66%). Group music therapy model enhances the group interactions and communications. Music intervention being one form of non-pharmacological approaches has several advantages in that it addresses the psychosocial as well as environmental aspects for managing behavioural problems. Music intervention, therefore, may have provided an avenue for appropriate expression of negative emotions.